The Contestation of Hadith Reason and Science in the Case of Ruqyah: Kontestasi Nalar Hadis Dan Sains Dalam Kasus Ruqyah - Muawanah, Arofatul (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
Ruqyah has long been practiced even before the establishment of Muhammad's prophethood. Even now, with the characteristics of modern society that tends to be rationalist, ruqyah remains an option when medical treatment efforts have been carried out but have not yielded results. Seeing the considerable public interest and interest in the practice of ruqyah, indicates that the existence of ruqyah can be accepted and felt the benefits by modern society. The purpose of this study is to reason the existence of ruqyah in hadith literature and to reason how ruqyah can be accepted in the perspective of science. This research is a type of qualitative research using a library research approach. Data collection is carried out by looking for references that have conformity with the research theme, namely explanations of ruqyah in the Prophet's hadith, laws and practices justified by the Prophet of Allah; and how the truth of ruqyah is acceptable to reason and science. This research yielded several things. First, that religion permits the practice of ruqyah as long as the recitation is spoken in accordance with the guidance of the Shari'ah and does not contain shirk. Secondly, the practice of ruqyah is justified in the point of science, including water as a medium in ruqyah has the ability to capture messages around it, the prayers recited are able to affect one's body and ruqyah has similarities with hypnotherapy.